Recriar a vida... reinventar a pré-escola: (buscando caminhos para a pré-escola popular) - Tiriba, Lea (1988)
This work is the account of an experiment in popular education in a community kindergarten in a Rio de Janeiro favela. A brief outline of the social context In which the experiment took place is followed by a description and analysis of the three points which were considered to be crucial to the project: i) the development of a pre-school pedagogy based on local conditions and culture; ii) the creation of lay teachers, and preparing them for autonomy; iii) the formation of a closer relationship between school and community, in an attempt to reestablish the union between knowledge and life. Practice, reflection on practice, the incorporation of theoretical knowledge, and the search for democratic relationships between the members of the team of educators all led to the discovery of certain points of reference, and of certain ways towards a pre-school experience committed to complete and integral education of the lower classes.